Long-Pulse Gastric Electrical Stimulation Repairs Interstitial Cells of Cajal and Smooth Muscle Cells in the Gastric Antrum of Diabetic Rats - Yan Chen; Hongcai Wang; Hai Li; Shi Liu (Gastroenterology Research and Practice)
Background/Aims. The damage of interstitial cells of Cajal and smooth muscle cells has far-reaching implications in the pathogenesis of gastroparesis in diabetic patients. Gastric electrical stimulation (GES) is an efficient therapy for gastric motility disorders, but the mechanisms of GES require clarification. Methods. Male rats were randomly divided into the control group, diabetic rat group (DM), diabetic rats with sham GES group (DM + SGES), and diabetic rats with different frequency GES group (DM + GES) (GES1: 5.5 cpm, 100 ms, 4 mA; GES2: 5.5 cpm, 300 ms, 4 mA; and GES3: 5.5 cpm, 550 ms, 2 mA). Gastric contractions were explored using the organ bath technique. The alterations of interstitial cells of Cajal, the SCF/c-kit pathway, and smooth muscle cells were also investigated. Results. (1) Gastric contractions were significantly improved in the DM + GES group compared with those in the DM group. (2) The damage of interstitial cells of Cajal was prevented in the DM + GES group in contrast to the DM group. Moreover, long-pulse GES increased the expression of the SCF/c-kit pathway. More proliferated interstitial cells of Cajal in muscle layers were observed obviously in the DM + GES group. (3) The number of smooth muscle cells in the DM group was not significantly decreased compared with that in the control group. However, ultrastructural changes were distinctly damaged in the DM group. The application of GES protected against the alteration of the ultrastructures of smooth muscle cells. Conclusions. Long-pulse GES improves gastric contraction possibly by enhancing the proliferation of interstitial cells of Cajal and restoring the injury of smooth muscle cells.